2012
DOI: 10.1097/id.0b013e31824bf93c
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Linear Measurements in Cone Beam Computed Tomography With Different Voxel Sizes

Abstract: The accuracy of vertical and horizontal measurements, using CBCT (i-CAT) for the four protocols, was shown to be comparable with the measurements performed on the dry mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 19 publications
9
63
2
3
Order By: Relevance
“…Patcas and colleagues [11] (evaluating both bone height and width) showed that 0.4-mm voxel images provided results as accurate as 0.125-mm voxel images. This finding is also in agreement with Torres and coauthors [33], who did not find differences between voxel sizes of 0.2, 0.3, and 0.4 mm, when evaluating linear bone measurements.…”
Section: Assessment Methods Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Patcas and colleagues [11] (evaluating both bone height and width) showed that 0.4-mm voxel images provided results as accurate as 0.125-mm voxel images. This finding is also in agreement with Torres and coauthors [33], who did not find differences between voxel sizes of 0.2, 0.3, and 0.4 mm, when evaluating linear bone measurements.…”
Section: Assessment Methods Resultssupporting
confidence: 82%
“…The remaining eight studies were based on numerical outcomes measured in the images. Three studies measured 3D surface reconstructions [17,30,31] (and used micro-CT of the teeth as the gold standard), two measured the height and thickness of alveolar bone [11,32], one assessed linear bone measurements (distance between established anatomical landmarks) [33], one measured the thickness of the soft tissue of the face [34], and one measured tooth and root length [35], and these last five studies used caliper measurements of the skulls as the gold standard. Six studies further compared the CBCT images in different resolutions to images acquired using intraoral radiographic systems [18,21,[25][26][27]35].…”
Section: Review Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Após esse período, cada mandíbula foi inserida em uma caixa de isopor (16 cm × 14,5 cm × 10 cm) contendo água, para manutenção do preenchimento dos espaços medulares. As mandíbulas foram posicionadas no interior da caixa de isopor de modo que o plano sagital mediano (PSM) ficasse perpendicular ao plano horizontal (PH), e o plano mandibular alcançasse uma inclinação de 25 graus em relação ao PH, simulando a orientação espacial da mandíbula in vivo (Figura 2) 6 . O conjunto foi levado ao tomógrafo e mantido em posição no cefalostato do aparelho.…”
Section: Materials E Métodounclassified
“…It may result in injury to the neurovascular bundle and cause some postoperative complaints such as neuroma, paresthesia, anesthesia and hemorrhage [4][5] . It has been stated that CBCT anatomical linear measurements are accurate and reliable [6][7][8][9][10][11][12][13] . However, the inclination of the patient's head during CBCT image acquisition can cause distortion in measurements for preoperative implant planning [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%